Factors that Cause Overweight and Obesity in School-Age Children and Adult: A Literature Review - Rifdah Dinda Qatrunnada (Media Gizi Kesmas, 2022)
Background: Obesity in children can affects their activities and motivation in learning at school. Obesity can also affect adulthood performance in their work skills and productivity. Early prevention of overweight in children is very important in order to maximize the quality of life when entering the adult age group.Objectives: The purpose of this study is to identify the factors causing the incidence of overweight and obesity in school-age children and adults so that it can be used as a guide to overcome health problems in those critical age group.Methods: This article was compiled based on the literature search in the last ten years and was carried out through Google Scholar and Science Direct, related to factors that can cause overweight and obesity in school-age children and adults.Discussion: The results from eighteen literature, it is known that unhealthy eating habits, food environment, physical activities, heredity or genetic factors, sleep duration, and family income can cause overweight and obesity in school-age children. While gender, level of education, heredity or genetic factors, physical activity, daily calorie intake, marital status, personal income, and urban living are the cause of overweight and obesity in adults.Conclusions: Factors that can cause overweight and obesity are gender, level of education, unhealthy eating habits, food environment, physical activities, heredity or genetic factors, sleep duration, family income, daily calorie intake, and marital status.